Gamifying fractions: the development of 'fraction heroes' for junior high learners - Muhardiffa, Azzahra; Zaura, Bintang; Elizar, Elizar (Nashir Al-Kutub Indonesia, 2025)
The application of digital technology in education has had a positive impact on improving learning outcomes. One form of technology integration in education is the use of educational games as interactive learning media. This study aims to develop the Fraction Heroes educational game using Unity software and to describe the quality of the developed product in terms of its validity and practicality. The method employed in this study is research and development (R&D), utilizing the ADDIE development model. The research subjects included expert validators in mathematics and educational technology, as well as seventh-grade students from two junior high schools in Banda Aceh. The research instruments consisted of expert validation sheets and student response questionnaires. The data were analyzed descriptively to assess the validity and practicality of the Fraction Heroes educational game. The results indicate that the Fraction Heroes game meets the criteria for validity and practicality as an instructional medium. The game can enhance student engagement in learning and offers an innovative alternative for teaching fraction concepts. This research suggests that integrating technology into mathematics instruction can enrich students’ learning experiences in a more interactive and enjoyable manner.